Make handling of post-pasteurized waste milk a priority - Elizondo Salazar, Jorge Alberto (2008)
All dairy operations have a supply of milk that is not saleable, commonly called waste or discard milk. Waste milk as documented in one study, can range from 48 to 137 pounds per cow per year, representing a huge economic loss to the dairy farm, disposal problems and environmental issues.